Analysis of Asset Management Ratio and Solvency Management Ratio - Saut Maruli Tua Pandiangan; Hotbona Novandi Tambunan; Josua Alexander Gultom; Thomas Firdaus Hutahaean (HM Journals, 2024)
Profit is total income after deducting company costs or what can be called net profit. Profits generated by a company can be a benchmark for a company's success. To gain large profits, a company must be able to manage assets effectively and efficiently, because this can show that the company has good financial performance. One of the ratios that investors most often consider is the total assets turnover ratio. However, often a high asset management ratio does not indicate the company's effectiveness in managing high assets, but because inventory levels are low. A company is said to be insolvent when its debt position is greater than the total assets owned by the company. To find out whether it is solvable or not, it can be calculated using the debt to equity ratio. PT FKS Food Sejahtera Tbk (IDX: AISA) is a food producing company headquartered in Jakarta, Indonesia. This company was founded in 1990, with the main products being various types of ready-made food. The purpose of this research is to analyze asset management ratio and solvency management ratio PT FKS Food Sejahtera Tbk. The type of research in this research uses qualitative descriptive research. The subject of this research is PT FKS Food Sejahtera Tbk whose financial report data is from 2015 to 2021. The object of this research is asset management ratio and solvency management at PT FKS Food Sejahtera Tbk. The analysis method in this research uses a time series analysis approach. The results of this research show that the average fixed asset turnover of PT FKS Food Sejahtera Tbk is 1.15 times. The average total asset turnover of PT FKS Food Sejahtera Tbk is 0.7 times. The average debt ratio at PT FKS Food Sejahtera Tbk from 2015 to 2017 has a value of 1.38 which becomes unsafe in 2017, 2018, and 2019. The multiple that received the highest profit was in 2019 with a multiple of 12.15.